2019
DOI: 10.1371/journal.pone.0212406
|View full text |Cite|
|
Sign up to set email alerts
|

Metagenomic analyses of the gut microbiota associated with colorectal adenoma

Abstract: Recent studies have suggested an association between certain members of the Fusobacterium genus, especially F . nucleatum , and the progression of advanced colorectal carcinoma (CRC). We assessed such an association of the gut microbiota in Japanese patients with colorectal adenoma (CRA) or intramucosal CRC using colonoscopy aspirates. We analyzed samples from 81 Japanese patients, including 47 CRA and 24 intramucosal CRC patients, and 10 hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(39 citation statements)
references
References 31 publications
2
37
0
Order By: Relevance
“…Inhibition of immune cells would be desirable for tumor cells, since it will spread the tumor to other parts of the body [ 112 ]. Investigation of 16 s rRNA sequencing of increased F. nucleatum levels in mucosal or fecal samples of CRC patients has shown that F. nucleatum levels in CRC tissue is associated with the tumor site of right-sided proximal colorectum and CpG island methylator phenotype ( CIMP ) status, microsatellite instability ( MSI ) and mutations in BRAF, KRAS, CHD7, CHD8 and TP53 genes [ 131 ]. Increased inflammatory cytokines such as NF-KB, TNF-α, IL10, IL8, IL6, and increased levels of E. cadherin on epithelial cells activates B-catenin signaling, increases NF-κB , C-myc expression and proliferates tumor cells [ 70 ].…”
Section: Factors Affecting the Intestinal Microbial Populationmentioning
confidence: 99%
See 1 more Smart Citation
“…Inhibition of immune cells would be desirable for tumor cells, since it will spread the tumor to other parts of the body [ 112 ]. Investigation of 16 s rRNA sequencing of increased F. nucleatum levels in mucosal or fecal samples of CRC patients has shown that F. nucleatum levels in CRC tissue is associated with the tumor site of right-sided proximal colorectum and CpG island methylator phenotype ( CIMP ) status, microsatellite instability ( MSI ) and mutations in BRAF, KRAS, CHD7, CHD8 and TP53 genes [ 131 ]. Increased inflammatory cytokines such as NF-KB, TNF-α, IL10, IL8, IL6, and increased levels of E. cadherin on epithelial cells activates B-catenin signaling, increases NF-κB , C-myc expression and proliferates tumor cells [ 70 ].…”
Section: Factors Affecting the Intestinal Microbial Populationmentioning
confidence: 99%
“…The direct association of Fusobacterium with recurrent CRC has even been postulated as a way to predict disease outcomes or change chemotherapy regimens such as inclusion of capecitabine and oxaliplatin for patients with a high burden of F. nucleatum [ 45 ]. These observations suggest further consideration of antimicrobial interventions as a potential treatment for patients with CRC related to Fusobacterium [ 131 ]. One concern is the negative effect of broad-spectrum antibiotics on the intestinal microbiome [ 20 ].…”
Section: Factors Affecting the Intestinal Microbial Populationmentioning
confidence: 99%
“…Using LEfSe, we found, for example, that Fusobacterium ( Fusobacteriaceae family), was more abundant at 10 days (LDA score > 3) in both metagenomics and metatranscriptomics data (Figure 3 ). The role of Fusobacterium on cockroaches’ gut microbiome deserve a detailed study due to these results and some interesting findings about this groups’ role in other organisms: Fusobacterium has been related to disease and stress situations in the human gut microbiota ( 48 ), but is has also been related to the infants gut microbiota ( 49 ). Conversely, an unidentified genus belonging to the family Ruminococcaceae , has been found more abundant in 20d than 10d condition (LDA score > 3) in metagenomics data (Figure 3A ), but no differences between conditions have been found in metatranscriptomics data (Figure 3B ).…”
Section: Resultsmentioning
confidence: 98%
“…Using LEfSe, we found, for example, that Fusobacterium (Fusobacteriaceae family), was more abundant at 10 days (LDA score > 3) in both metagenomics and metatranscriptomics data (Figure 3).. Fusobacterium has been related to disease and stress situations in the human gut microbiota [44], but is has also been related to the infants gut microbiota [45]. Conversely, an unidentified genus belonging to the family Ruminococcaceae, has been found more abundant in 20d than 10d condition (LDA score > 3) in metagenomics data (Figure 3a),, but no differences between conditions have been found in metatranscriptomics data (Figure 3b)..…”
Section: Comparison Of Metagenomics and Metatranscriptomics/metaprotementioning
confidence: 95%